Co-determination in Germany - A Beginner's Guide - Rebecca Page (Hans-Böckler-Stiftung, 2018)
The word "co-determination", or "Mitbestimmung" in German, is commonly heard outside of Germany but it's actual meaning is often unclear.This collection of texts aims to provide a basic explanation of what co-determination is all about, how it functions in practice and what it means to the Germans and to Germany as whole. The relationship between the German co-determination system and developments within Europe are also considered.
Additional information: Geringfügig veränderter Nachdruck der Ausgabe von 2011.
Keywords: 330